Construção de um instrumento de avaliação do estágio supervisionado hospitalar para unidade obstétrica - Leite, Marília Siebra Pereira (2019)
The objective of this research was to construct an instrument for the evaluation of the Supervised Internship in Nursing Care (ESAH) of Nursing graduation for Obstetric unit. For this, a methodological research was carried out with a qualitative approach interviewing Obstetrician Nurses of the University Hospital Lauro Wanderley-HULW and undergraduate Nurses of the tenth period of the Federal University of Paraíba - UFPB between the months of October and November of 2018. The thematic analysis of the data collected provided support in the construction of an ESAH assessment instrument specific to Obstetric Unit. The constructed instrument was submitted to semantic and content validation by judges with great experience in the subject that had the opportunity to maintain, delete or change some topics of the instrument. In this case, a concordance index of 75% have been used in order to judge if to keep or delete topics; all pertinent modification and addiction proposals made from judges have been included in the work. Prior to the research, the project was submitted to Plataforma Brasil and approved by the Hospital's Ethics and Research Committee through the deliberation nr 2.893.499, respecting the ethical aspects pertinent to research involving human beings established by Resolution 466 of December 12, 2012. The theoretical chapter follows the historical trajectory of Nursing teaching in Brazil presenting the main political changes that took place, discussing the competencies and skills expected in the training of nurses, according to the National Nursing Curricular Guidelines, linking to the philosophical theory Paulo Freire and, finally, discussing the Supervised Hospital Stage and the process of appraising the student's learning. Results of this research highlight fragilities and strengths of the ESAH in the Obstetric Department and create as a final product an evaluation instrument for Nurse student specific for Obstetrician Nursery. This instrument will drive the teachings of the nurse in the Obstetric unit of graduates of the tenth period, as well as assist in the evaluation of them during the supervised stage. Thus, it is hoped to contribute to improve the quality of the teaching-learning process of students, so that these future professionals will collaborate in the supply of health demands, generating integral actions, humanized, according to the current public policies advocated by SUS. In addition, the results of the research may help the Pedagogical Projects of the higher education institutions to drive the learning process in the hospital